Sproglige og fortælletekniske iagttagelser i Herman Bang’s novelle "Irene Holm" - Mortensen, Finn Hauberg (Poetik, 1969)
Sproglige og fortælletekniske iagttagelser i Herman Bang’s novelle "Irene Holm"